2017
DOI: 10.5380/biofix.v2i1.50761
|View full text |Cite
|
Sign up to set email alerts
|

Comparação De Métodos E Processos De Amostragem Para Inventário Em Floresta Ombrófila Mista

Abstract: RESUMO ABSTRACTInventários florestais são indispensáveis para avaliar quantitativa e qualitativamente os recursos existentes em determinada propriedade ou região. Diferentes métodos e processos aplicados aos inventários repercutem em estimativas com maior ou menor precisão. O objetivo deste estudo foi comparar as dimensões de unidades amostrais, sua distribuição na população e intensidades amostrais na estimativa da densidade, área basal e volume por hectare em um fragmento de Floresta Ombrófila Mista no Sul d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…It was found that the relative sampling error in all estimates performed was higher than the real error of the estimate. This feature was also observed by Sydow et al (2017) when comparing the sampling error with the census of a mixed ombrophilous forest fragment; these authors observed an overestimation of the sampling error, as in this work. It is also noteworthy that the sampling error reveals the probability that the sampling can adequately represent the population, but does not ensure the accuracy of the forest inventory estimates.…”
Section: Discusssionsupporting
confidence: 85%
“…It was found that the relative sampling error in all estimates performed was higher than the real error of the estimate. This feature was also observed by Sydow et al (2017) when comparing the sampling error with the census of a mixed ombrophilous forest fragment; these authors observed an overestimation of the sampling error, as in this work. It is also noteworthy that the sampling error reveals the probability that the sampling can adequately represent the population, but does not ensure the accuracy of the forest inventory estimates.…”
Section: Discusssionsupporting
confidence: 85%
“…66 Low NDVI values are related to disturbed forests by logging activities and wildfires that affect canopy cover. 17,64,67 High NDVI values are commonly observed in undisturbed forest sites, [67][68][69] as observed in this study within DLOF. The high correlation result between vegetation indices and AGB observed in our analysis is accordance with the available scientific literature.…”
Section: Discussionsupporting
confidence: 67%
“…42 Based on the high complexity of the studied variables and the high variability commonly observed in tropical forests, we considered an error limit of ∼20% acceptable, which indicates an achievement of robust prediction results. 26,68 The ANN has been applied by several studies in forest environment showing high predictive power compared to classical regression models for estimating variables of interest. 21,26,27,75,76 In addition, the ANNs and remotely sensed data combined can provide higher modeling precision in forest sites than the regression models, as they are able to assimilate a high complexity and variety of vegetation, environment, and climatic aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the known sampling methods, the fixed-area method is the oldest and most widespread one in Brazil; the selection of trees is made according to the frequency in which the trees are arranged in the forest and to the size of the sampling unit (SANQUETTA et al, 2014). This method is widely cited in the forest literature and considered, in several cases, as a comparator in different studies, as in the works of Moscovich et al (1992), Druszcz et al (2010), Nakajima et al (2011), Santos et al (2013, Téo et al (2014), Miranda et al (2015), Sydow et al (2017), andOliveira et al (2019).…”
Section: Introductionmentioning
confidence: 99%